COUNTER-HEGEMONIC DISCOURSE: A CASE STUDY OF RELOCATION OF GOVERNMENT CAPITAL TO CENTRAL KALIMANTAN - Linggua Sanjaya Usop (Journal SOSIOLOGI, 2018)
Counter to the hegemony of the Dayak community in Central Kalimantan, if it is being the capital government of the Republic of Indonesia is intended to safeguard the rights of the Dayak people who essentially have two opposing sides. On the one hand, it is counter hegemony, to give greater attention to development of indigenous Dayak lands, recognition of Dayak cultural identity, providing a large space to implement local authority. However on the other hand, it can be a kind of institutionalization to strengthen rights of natural and land resource management, in the sense that they continue to strengthen the ethnic spirit of Dayak and ethnic identity, which may be counterproductive with the aim of strengthening the sentiments of nationalism and Indonesian identity. Recognition and protection of indigenous people is part of a constitution that recognizes the existence of indigenous peoples and their rights. Recognition of customary law communities and their traditional rights must be based on the principle "remaining the frame of the Unitary State of the Republic of Indonesia". This principle emphasizes that indigenous peoples and tribes are part of the Indonesian state whose position is very influential and guaranteed by the constitution in developing political, social, economic, legal, and human rights to achieve defense and security.